PENGARUH GAME BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS : SYSTEMATIC LITERATURE REVIEW - Nuraeni; Hepsi Nindiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Game-Based Learning (GBL) on students’ mathematical creative thinking skills through a Systematic Literature Review (SLR) covering the period 2020–2025. The research employed a qualitative approach with an SLR design, where the data sources consisted of scientific articles obtained from Google Scholar, Semantic Scholar, and SINTA databases. A total of 13 articles that met the inclusion criteria were systematically analyzed through identification, selection, evaluation, and data synthesis stages. The results indicate that the implementation of GBL generally has a positive impact on students’ mathematical creative thinking skills, as reflected in improvements in creativity indicators such as idea fluency, flexibility in problem-solving, originality, and the ability to generate multiple solution alternatives. In addition, GBL has been proven to enhance students’ motivation, engagement, and interest in learning mathematics. However, the level of improvement varies depending on instructional design, media suitability, as well as student characteristics and learning environments. Other findings reveal that the effectiveness of GBL can be optimized when combined with approaches such as STEM, ethnomathematics, and Challenge-Based Learning. This study contributes theoretically to strengthening constructivist learning concepts and practically as a reference for educators in developing innovative instructional strategies.